Academic use of smartphones by university students: a developing country perspective. Issue 4 (1st August 2016) - Hossain, Md. Emran; Ahmed, S.M. Zabed
Abstract : Purpose: This paper aims to investigate the use of smartphones for academic purposes by students at Dhaka University, the top-ranked university in Bangladesh. Design/methodology/approach: Students currently using smartphones answered a questionnaire survey, which focused on whether or not students used smartphones for academic works and, if so, for what purposes they used them and their opinion on the advantages of using smartphones for academic purposes. Descriptive statistics were used to analyze demographic and academic characteristics of the students in relation to their smartphone usage. Non-parametric analyses were performed using Mann–Whitney and Kruskal–Wallis tests to compare between students' demographic and academic variables and their opinion on the advantages of academic use of smartphones. Findings: The findings indicate that a vast majority of university students used smartphones for academic purposes. They, on average and across the board, had a positive perception toward academic use of smartphones. Although there were some differences in terms of gender, age, place of origin and duration of smartphone use, these differences were largely due to fact that a smartphone is a relatively new addition to the life of most students who participated in this study. Originality/value: Research investigating the academic use of smartphones in the perspective of developing countries is virtually non-existent. This is the first time an effort has been made to examine the use of smartphones by a large sample of university students in Bangladesh.